Negative Self-Disclosure on the Web: The Role of Guilt Relief - Levontin, Liat; Yom-Tov, Elad (Frontiers in Psychology, 2017)
In this paper, we suggest people use anonymous online forums as platforms for self-disclosing actions they feel guilty about—such as transgressions and unethical behaviors—with the goal of achieving guilt relief through others’ reactions. We support this proposition by analyzing field data extracted from Yahoo Answers, an online question-and-answer website. Our analysis shows the level of guilt relief an answer is expected to offer the “asker” (the self-disclosing person) is positively associated with the asker’s likelihood of selecting that answer as the “best” response to the self-disclosure. Furthermore, following receipt of a guilt-relieving answer, an asker becomes less likely to engage in prosocial behavior, which is another type of guilt-relieving action.